Management of Acute Coronary Syndrome Following Blunt Chest Trauma: A Case Report - Chan, Ee Lyn (Bull Emerg Trauma, 2021)
Blunt chest trauma is a rare cause of acute coronary syndrome and can be masked by other injuries in polytrauma patients. It can have devastating consequences due to damage to the myocardial tissue if left un-recognized. Myocardial injury can result in life-threatening arrhythmias and complications such as systolic and diastolic dysfunction. This can significantly affect patients’ quality of life. A 34-year-old man involved in a paragliding incident in Kazakhstan. His equipment failed at 30 meters height and result him to be propelled at high velocity to the ground. He sustained multiple injuries including spinal fractures, lung contusions and a mediastinal haematoma. He was transported to a local hospital and noted to have ST segment elevation on his admission electrocardiogram (ECG). He underwent an angiogram that showed sub-occlusion of his left anterior descending (LAD) artery. This resulted in a time-critical Percutaneous Coronary Intervention (PCI). He was stabilized and repatriated to the UK to manage of remaining injuries.